2014
DOI: 10.3390/ijms151121286
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Levels of Interleukin-8 Are Associated with Hepatitis B Virus Infection and Resistance to Interferon-Alpha Therapy

Abstract: The objective of this study was to analyze the expression levels of IL-8 in serum and liver tissues from patients with chronic hepatitis B (CHB) infection and to investigate whether IL-8 may antagonize interferon-alpha (IFN-α) antiviral activity against HBV. IL-8 expression in serum was determined by enzyme linked immunosorbent assay (ELISA), and fluorescence-based quantitative real-time PCR (RT-qPCR) was used to measure IL-8 mRNA in peripheral blood mononuclear cells (PBMCs) in patients with CHB. IL-8 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…9 The level of IL-8 in nasal secretion was ∼40 times higher compared with the level of IL-8 in normal blood samples. 40 Based on our results, the level of HSP70 in nasal secretion was ∼60 times higher compared with previously reported levels of blood HSP70. 41 Although the normal value of HSP70 in nasal lavage fluid samples is not yet determined, we found that the level of HSP70 was much lower in control subjects compared with patients with CRS (data not shown).…”
Section: Discussionsupporting
confidence: 43%
“…9 The level of IL-8 in nasal secretion was ∼40 times higher compared with the level of IL-8 in normal blood samples. 40 Based on our results, the level of HSP70 in nasal secretion was ∼60 times higher compared with previously reported levels of blood HSP70. 41 Although the normal value of HSP70 in nasal lavage fluid samples is not yet determined, we found that the level of HSP70 was much lower in control subjects compared with patients with CRS (data not shown).…”
Section: Discussionsupporting
confidence: 43%
“…IL-8 is a chemokine, which plays a crucial role in the activation of neutrophils and their recruitment to the inflammation site, and its expression increases with the staging of fibrosis. 44 IL-8 mediates the recruitment of various inflammatory cells like Th, which secretes inflammatory mediators, including IL-1, leading to repeated inflammation and damage to liver function, 45,46 whereas IL-10 is an anti-inflammatory cytokine that was also found to be increased after micelle treatment. Increased IL-10 has been reported upon systemic administration of siRNA in general.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 contributes to liver inflammation and fibrosis by increasing the accumulation of CD181 + macrophages in the liver [ 48 ]. Interestingly, the levels of IL-8 are increased during HBV infection [ 49 ], which suggests that IL-8 might be causing an accumulation of CD181 + macrophages in the HBV-infected liver. Of note, polymorphism in the CXCR1 gene was found to be associated with the disease activity during chronic HBV infection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%